Exploring the cultural and linguistic dimensions of phraseological somatisms: a comparative analysis of english and uzbek languages - Sabirova, M.R (SCIENCE and SOCIETY, 2025)
The article delves deeper into the world of phraseological somatisms in English and Uzbek, providing a comparative analysis of these unique linguistic phenomena. Through a systematic analysis of selected somatic expressions, the role of phraseological somatisms in enriching language use and developing intercultural understanding is highlighted.
Keywords: phraseological somatisms; comparative analysis; English language; Uzbek language; cultural implications; linguistic diversity; metaphorical concepts; embodied experiences; syntactic structures; cross-cultural communication; language usage; semantic meanings